Baby beebee bird (The) - Massie, Diane Redfield (New York : Random House, 1963)
What does the baby beebee bird sing? He sings beebeebobbi, beebeebobbibobbi, all night long. He's the funniest bird you ever heard!
Keywords: Bird-Stories; Bird-Fiction